The relationship between Jim Crow laws and social capital from 1997–2014: A 3-level multilevel hierarchical analysis across time, county and state. (October 2020) - Hswen, Yulin; Qin, Qiuyuan; Williams, David R.; Viswanath, K.; Brownstein, John S.; Subramanian, S.V.
Abstract: Introduction: Jim Crow laws in the United States promoted racial prejudice, which may have reduced social capital. Our study tests the relationship between Jim Crow laws and social capital. Methods: We conducted 3-level multilevel hierarchical modeling to study differences in the stock of social capital for 1997, 2005, 2009 in Jim Crow states compared to states without Jim Crow laws. We examined the moderation effects of county level median income, percent Black and percent with high school education and Jim Crow laws on social capital. Results: Jim Crow laws significantly reduced stock of social capital across 1997, 2005, 2009. The model was robust to the inclusion of random county, states, time and fixed county and state level covariates for median income, percent Black and percent with high school education. The largest percent of between state variations explained for fixed variables was from the addition of Jim Crow laws with 2.86%. These results demonstrate that although Jim Crow laws were abolished in 1965, the effects of racial segregation appear to persist through lower social connectiveness, community and trust. A positive moderation effect was seen for median income and percent Black with Jim Crow laws on social capital. Discussion: Our study supports a negative association between Jim Crow laws and reduction in the stock of social capital. This may be attributed to the fracturing of trust, reciprocity and collective action produced by legal racial segregation. Findings from this study offer insight on the potential impacts of historical policies on the social structure of a community. Future research is necessary to further identify the mechanistic pathways and develop interventions to improve social capital. Highlights: Jim Crow laws enforced racial prejudice, and significantly reduced social capital . Rising social capital among Jim Crow states may be due to increases in equality. Although Jim Crow laws were abolished in 1965, the negative social effects persist . Our study highlights the racist historical policies have detrimental effects on community trust and reciprocity.